Phylogenetic survey of metabolically active microbial communities associated with the deep-sea coral Lophelia pertusa from the Apulian plateau, Central Mediaterranean Sea - YAKIMOV M. M.; CAPPELLO S.; CRISAFI E.; SAVINI A.; CORSELLI C.; SCARFI S. AND GIULIANO L.; TURSI, Angelo Raffaele (Deep Sea Research Part I: Oceanographic Research Papers, 2006)
Living deep-water coral assemblages were discovered recently inhabiting the Mediterranean Sea between the depths of 300 and 1000 m off the Cape of Santa Maria di Leuca (Apulian platform, Ionian Sea). This living assemblage was dominated by two colonial scleractinian corals, Lophelia pertusa and Madrepora oculata. Two other corals, Desmophyllum crystagalli and Stenocyathus vermiformis were also recovered from this site, but were much less common. The composition of the metabolically active fraction of the microbial community associated with living specimens of L. pertusa was determined. Dead corals, proximal sediments and overlying seawater were also sampled and analyzed. Complementary 16S ribosomal DNA (crDNA) was obtained from total RNA extracted from all samples that had been subjected to reverse transcription-PCR amplification. Domain-specific 16S PCR primers were used to construct four different 16S crDNA libraries containing 45 Archaea and 201 Bacteria clones. Using Archaea-specific primers, no amplification products were obtained from any coral samples (live and dead). Living specimens of L. pertusa seem to possess a specific microbial community different from that of dead coral and sediment samples. The majority of all coral-associated riboclones was related to the Holophaga-Acidobacterium and Nitrospira divisions (80%). Moreover, more than 12% of all coral-associated riboclones formed a separate deep-branching cluster within the α-Proteobacteria with no known close relatives. The metabolically active fraction of the bacterial community colonizing the dead corals was dominated by Proteobacteria related to the gamma and epsilon subdivisions (74% and 26% of all clones, respectively). Phylogenetic analysis of the Archaea clone library retrieved from proximal sediments indicated an exclusive dominance by the members of Crenarchaea Marine Group I (MGI), a lineage of unculturable microorganisms, widely distributed in marine habitats. In contrast, bacterial diversity was considerably higher in this sample than ...